Relação da prematuridade com o perfil antropométrico e metabólico de adolescentes em seu contexto de vida - Lopes, Mírian Nara (2018)
Faced with technological development and professional training, it has been possible to guarantee a higher survival rate of preterm newborns, reducing mortality and morbidity. However, premature born people often present changes in growth and metabolism that will have repercussions on their health throughout life. In this sense, premature born adolescents may have a greater chance of developing obesity and its comorbidities. Thus, the present study aims to identify the repercussions of prematurity on the blood pressure (BP), lipid, glycemic and anthropometric profiles in adolescents living in a neighborhood in the city of Cascavel, according to their socioeconomic conditions. For that, a quantitative cross-sectional descriptive study was carried out at a Basic Health Unit in Cascavel, considering 50 preterm adolescents from 10 to 19 years old. Data collection was performed through semi-structured interview, physical evaluation (physical examination and collection of exams) and information from the vaccination portfolios. Data were analyzed by descriptive statistics and the correlations by inferential statistics; level of significance of 5% (p> 0.05) and 95% confidence interval. Findings showed 52% male, mostly white (54%), born with gestational age from 32 to 36 weeks (80%) and with adequate weight for gestational age (70%). Most of them used to have their meals in front of the screens (78%), and only 18% practice physical activity three times a week. In their personal history, 62% report respiratory issues and 58% have some type of allergy. In physical examination, 30% were overweight, 10% had abdominal circumference (AC) in the 90th percentile, 34% had high blood pressure (BP), 41% presented high triglycerides (TG) and 22% had high total cholesterol TC); only one adolescent presented altered glycemia. An association between the degree of prematurity and the classification of BP (p-value = 0.027) and trend of association with TG (p-value = 0.05) was identified. Higher proportion of overweight is related to adolescents born extremely or very premature, and 60% of them presented elevated blood pressure. Among the big sized preterm during gestational age, 44,4% showed increased BP, TC and TG. The small sized prematures didn’t show elevated BP. An important statistical association was observed between blood pressure and the number of meals (p=0,01), total cholesterol and breastfeeding (p=0,03), and triglycerides with consumption of sausages (p=0,02) and products rich in carbohydrates (p=0,01). 72% were offered cow's milk before one-year-old and only 30% received exclusive breastfeeding until six months; no statistical difference was observed related to the breastfeeding type and the variables investigated. Among the 30% with overweight, 60% had elevated BP, 53% TG, 33% CT and 33% WC ≥ 90th percentile. TG rates showed a relation with the family income and maternal schooling. Thus, for those with incomes up to a minimum wage there was a higher concentration of elevated TG, while the highest TG values were found in those whose mothers had higher schooling. The present study showed that a significant proportion of preterm infants presented high blood pressure and lipid profile and excessive body weight, a situation that exposes them to a higher risk of developing metabolic syndrome in adulthood and to become part of the group of adults with health chronic conditions.